2022
DOI: 10.1039/d2ce00331g
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional magnetism in a facile spin 1/2 Heisenberg antiferromagnet with a low saturation field

Abstract: This work reports the synthesis, structure and magnetic properties of the single crystal of a facile spin 1/2 one dimensional Heisenberg antiferromagnet bis(4-aminopyridinium) bis(oxalato)cuprate(II) dihydrate, (C5H7N2)2[Cu(C2O4)2].2H2O. Single crystals of large...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The structure of copper acetate was confirmed with single crystal x-ray diffraction. Fourier transform infrared spectroscopy and Raman spectroscopy was done to identify the prominent relevant bonds in the structure that were confirmed by density functional theory calculations employing a mixed basis having a metal centre and an organic part [31,32]. Further, delocalisation index was calculated for different bonds and it was found that the delocalisation index value for direct Cu-Cu bonds was much lower than other bonds implying that the probability of direct Cu-Cu exchange in copper acetate is quite small.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The structure of copper acetate was confirmed with single crystal x-ray diffraction. Fourier transform infrared spectroscopy and Raman spectroscopy was done to identify the prominent relevant bonds in the structure that were confirmed by density functional theory calculations employing a mixed basis having a metal centre and an organic part [31,32]. Further, delocalisation index was calculated for different bonds and it was found that the delocalisation index value for direct Cu-Cu bonds was much lower than other bonds implying that the probability of direct Cu-Cu exchange in copper acetate is quite small.…”
Section: Introductionmentioning
confidence: 95%
“…DFT calculations have been done on the crystal for geometric optimisation and simulation of Raman and IR spectrum by Becke three-parameter Lee Yang Parr functional correlation, a well-known functional in DFT for calculating exchange-correlation energy [38,39]. To correctly incorporate the effect of a metal centre (Cu 2+ ) and organic ligands (oxalate and acetate), we used a dual basis, with LANL2DZ for the metal centre and 6-311++G(d,p) [40][41][42] for the rest of the atoms (organic part) [31,32,43,44]. The above choice of functional and basis set was made since they are routinely used to describe metal-organic crystals and are additionally less computationally intensive [45,46].…”
Section: Computational Detailsmentioning
confidence: 99%